Efeitos do programa Isupport-br na sobrecarga, sintomas depressivos e ansiosos de cuidadores informais de pessoas que vivem com demência: ensaio clínico randomizado - Rocha, Luana Aparecida da (2024)
Informal caregivers of people living with dementia are exposed to physical and emotional health problems, as the disease progresses, the people being cared for require greater support in activities of daily living, and caregivers often do not receive adequate support to this coping, which can develop greater perceptions of overload and anxious and depressive symptoms. Therefore, accessible tools such as the iSupport for Dementia online program are necessary to overcome barriers imposed on these caregivers, whether socioeconomic, physical or access to information, and provide education, development of socio-emotional skills and social support. Objective: To analyze the effects of the iSupport program, adapted for Brazil, on the burden, depressive and anxious symptoms of informal caregivers of people living with dementia. Method: This randomized clinical trial was carried out from January 2022 to July 2023, with a sample of 162 informal caregivers of people living with dementia, from all regions of Brazil, randomly allocated into two groups: intervention (n = 77) and control (n = 85). The intervention group (IG) had free access and use of the iSupport-Brasil (iSupport-BR) platform for three months. Simultaneously, the control group (CG) accessed the website of the Brazilian Alzheimer's Association (ABRAz) and the Care Guide for the Elderly. Pre- and postintervention assessments were carried out, consisting of sociodemographic data, burden assessment - Single-item Scale and Zarit Burden Interview (ZBI) and assessment of anxious and depressive symptoms (Hospital Anxiety and Depression Scale - HADS). All ethical procedures were respected. Results: The majority of caregivers were from the Southeast Region, with an average age of around 50 years, the majority were female, married, highly educated (12 years or more of study) and of white ethnicity. For the IG, the intention-to-treat (ITT) analysis demonstrated a significant decrease in anxiety in the post-test (p=0.02). The analysis per protocol (pp) also demonstrated a significant decrease in overload (ZBI p<0.01) and anxiety (p<0.01) for the GI in the post-test. No statistically significant effects were found for depression in the GI, although the scores decreased (p=0.09, p= 0.07 – pp and ITT respectively). For the CG, the regression model estimates indicate that, on average, there is a worsening of scores except for anxiety. Conclusion: The iSupport-BR program is effective in reducing the perception of overload and symptoms such as anxiety. Therefore, its use within the family context is recommended for informal caregivers of people living with dementia as an alternative support based on issues of education and development of socio-emotional skills. Future research with samples in other contexts, such as social/economic vulnerability and low education, may contribute to the consolidation of the iSupport-BR program for caregivers of people living with dementia in Brazil.